Fluence rate dependence of red light-induced phosphorylation of plasma membrane H+-ATPase in stomatal guard cells. (1st February 2019) - Ando, Eigo; Kinoshita, Toshinori
ABSTRACT: Stomatal opening is induced by red light as well as blue light. Recently, we established an immunohistochemical technique using whole leaves to study plasma membrane (PM) H + -ATPase in guard cells, which is an important enzyme driving stomatal opening. Our technique revealed that red light illuminated to whole leaves induces photosynthesis-dependent phosphorylation of C-terminal penultimate residue of PM H + -ATPase, threonine, in guard cells, which has been considered to be important for activation of PM H + -ATPase, and we proposed that red light promotes stomatal opening via activation of PM H + -ATPase in guard cells in whole leaves. Here, using our new immunohistochemical technique, we investigated fluence rate dependence of red light-induced phosphorylation of PM H + -ATPase. We found that illumination of red light at 50 µmol m –2 s –1, which was suggested to initiate photosynthesis, saturates phosphorylation of PM H + -ATPase. Furthermore, we immunohistochemically confirmed decrease in the amount of PM H + -ATPase protein in a knock-out mutant of AHA1, an isogene encoding the major isoform of PM H + -ATPase in guard cells, implying the importance of AHA1 as the major PM H + -ATPase protein in guard cells for light-induced stomatal opening.